(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The audit committees are considered to be one of the most important committees because of the role they play in supervising and monitoring the process of formation of the financial statements and correction of the internal supervising system also strengthening the independency of the internal and external audit. Matters which increases the efficiency and integrity of the financial statements which reflects positively on competence of board of directors and then enhance the position of the company through increasing the trust of the users of the financial statement within the company. Therefore, this research deals with the evaluation of the performance of the audit committees in Iraqi banks according to the local rules and international standards in order to identify the performance of these committees. The goals of this research into clarify the nature of the work of the audit. Comities, its goals, task and its formation. Also to shed a lite the tasks of the committee which were mentioned in international laws and standards related to it, and identifying the actual work of the audit committees that contains the instructional guide and the rules of professional conduct and the committee report, also designing evaluation model for the performance of the audit comities and applying it in Baghdad bank and Middle East Bank. As well as, the application of the specimen in the evaluation of the performance of the committee at the Bank of Baghdad and the Bank of Middle East to get to know the performance of the committees.